PENGARUH SEKTOR PARIWISATA, SEKTOR INDUSTRI, DAN SEKTOR KEUANGAN TERHADAP PERTUMBUHAN EKONOMI KOTA PAREPARE - Fitriani, Fitriani (Universitas Muhammadiyah Parepare, 2018)
This study aims to determine the effect of the Tourism Sector, the industrial sector and the Financial Sector on the economic growth of Parepare City from 2004-2016. This type of research is quantitative research. The object of this study was the Regional Government of the City of Parepare, data collection techniques using documentation to collect reports on the 2004-2016 Gross Regional Domestic Product in the City of Parepare, and unstructured interviews with employees at the Parepare City Youth Youth Sports and Tourism Office, Parepare City Trade Office , The One Door City of Parepare Investment Services and Integrated Services Office, Parepare City Regional Finance Agency Office, and the Parepare City Central Bureau of Statistics Office. The results of this study indicate that (1) the tourism sector has a negative and significant effect on the economic growth of the city of parepare which is regressed as a whole, while the tourism sector has a positive and significant effect obtained from the simple regression method in which the research year is divided into two parts, namely the 2004 period 2011 and period II 2012-2016, (2) The Industrial Sector has a positive and significant effect on the economic growth of the city of Parepare, and (3) the Financial Sector has a negative and insignificant effect on the economic growth of the city of Parepare.